Hey Arnold! Season 2 [videorecording (DVD)] - Bartlett, Craig (Paramount, 2018)
The adventures continue in the Season Two collection of Hey Arnold! Spend more time in the hood with Arnold and his best buddy Gerald as they endure playground bullies, secret crushes, and everything else that comes with big-city life. So don a cap, unbuttoned flannel, and head for the TV, because it's the only collection that answers the age-old question: How many people does it take to save a runaway pig from becoming bacon?